Effect of Temperature and Printing Angle in FDM Additive Printing on the Strength Properties of PET-G - Patryk Krawulski; Katarzyna Panasiuk; Mirosław Tyliszczak (Scientific Journal of Gdynia Maritime University)
3D printing, also known as additive printing or additive manufacturing, has become an integral part of today’s manufacturing technologies, enabling rapid and flexible fabrication of three-dimensional objects from a variety of materials. Its importance in many fields is steadily increasing due its capabilities in prototyping, custom manufacturing and product personalisation. With the development of 3D printing technology, it is increasingly being used in the manufacture of marine machine parts and equipment. Before such products are implemented for real-world use, they require a thorough analysis of strength properties. In this work, the strength properties of the PET-G material were analysed with a change in temperature and printing angle using FDM (fused deposition modelling). Preliminary analysis of the results identified the best printing angle setting and the optimum choice of printing temperature.